Prenatal exposure to methanol as a dopamine system sensitization model in C57BL/6J mice - Mackey, Veronica R. (2012)
AIMS: In this study, the effects of prenatal exposure to methanol (MeOH) on the nigrostriatal dopamine (NSDA) system were examined to determine if the interaction could sensitize this system, and serve as an underpinning for Parkinson's disease (PD) like changes that occur later in life. Methanol was studied because its toxicity resembles the symptoms of PD and the symptoms are relieved by l-dopa meaning that MeOH targets the NSDA system. Since fermentation and wood combustion are major sources for MeOH, the incidence of human encounters with MeOH is high. As a superior solvent and the precursor for formaldehyde, MeOH has a powerful and sometimes, irreversible impact on chemical processes, such as cross-linking proteins and nucleic acids. It may cause subthreshold changes that sensitizes the NSDA system to PD, that occur during aging. MAIN METHODS: To study the prenatal effects of MeOH, pregnant C57BL/6J mice were administered 40 mg/kg MeOH by oral gavage during gestation days 8–12, twice daily. Twelve weeks after birth, behavior impairments were recorded. The striatum was dissected for the determination of tyrosine hydroxylase (TH), l-aromatic amino acid decarboxylase (LAAD), α-synuclein and levels of dopamine (DA) and its metabolites. KEY FINDINGS: MeOH reduced striatal TH and LAAD protein by 47% and 57% respectively and DA by 32%. SIGNIFICANCE: The results mean that in utero exposure to toxins similar to MeOH could sensitize the striatal system to changes that cause PD. This study may help identify strategies to block this type of in utero toxicity.